Dialog antar umat beragama sebagai karya pelayanan Gereja - Cangkung , Kristian Paskalis (Pastoralia, 2025)
This article aims to present perspectives on interreligious dialogue as a work of the Church’s ministry. In this view, interreligious dialogue is placed within the framework of the meaning and function of the Church’s presence in the world—namely, to serve humanity—not only within the Christian community but in its unity and wholeness, body and soul, heart and conscience, mind and will. In other words, the Church does not exist for itself but to build and serve the Kingdom of God, which has already begun in this world. Through dialogue, the Church concretely realizes itself in the history of humankind and radiates its identity as a vocation of the Holy Spirit that becomes a sign for the world. Through various dialogical efforts at all levels, the Church increasingly makes itself a sign and instrument of solidarity among religious communities in facing the challenges of our time—such as injustice, poverty, economic inequality, environmental damage, and moral degradation.